Genetic characterization of fin fish species from the Warri River at Ubeji, Niger Delta, Nigeria (2014)
A study to evaluate the genetic similarities and differences among 11 specimens of cichlids and four specimens of mudcatfishes obtained from Warri River was carried out through DNA fingerprinting analysis using random amplified polymorphic DNA (RAPD) amplification with seven decamer primers and dendrograms through unweighted pair-group method with average (UPGMA) cluster analysis. The total number of bands generated by seven RAPD primers, ranged between 2 to 33 for the cichlids and 8 to 28 for catfish family, with band size between 100 to 800 bp. The primers produced 228 bands in total 119 for cichlids and 109 for the catfishes, with 24% polymorphism. Considerable genetic variation was observed within species (especially within Tilapia Zilli, T. guineesis and Clarias gariepinus), between species in same genera (T. zilli and T. guineensis ) and among cichlids and catfishes. The most consistent of the RAPD primers generated 87 bands among the cichlids with 23 bands (26%) polymorphic and 74% conserved. Among the catfishes, the primers produced 69 bands with 16 (23%) polymorphic. The data show that the RAPD technique was useful and sensitive in differentiating various fish genera and species.